Feelings Matter: How Curatorial Practice can be Informed by Insights on the Dynamics of Artists’ Emotional Experiences - Little, Pippa; Moore, Sarah; Fitzpatrick, Mike (Irish Journal of Arts Management and Cultural Policy, 2014)
This article uses evidence from six visual artists’ own accounts of their artistic processes, in order tentatively to propose that there may be a commonality of emotional experience when it comes to producing artistic work. Through qualitative analysis we generated six categories of feelings that artists appeared to experience as they worked through the artistic cycle. This paper names and categorises the articulated feelings that appeared common to the artists. For each individual artist, we were able to identify feelings of engagement, disengagement, fear, a sense of constriction, freedom and relief. The emotional experiences associated with producing artistic work have been underexplored in the literature to date and we argue that knowledge about common feelings associated with producing artwork could be extremely useful, both for artists themselves and for curators. By recognising and naming feelings associated with different stages of the artistic process, both artists and curators might be more self-aware and facilitators or artistic mentors, including curators, might be more equipped to normalise the ‘artistic struggle’, to anticipate moments of motivation and to encourage persistence in the face of perceived obstacles. The implications of these findings for contemporary curatorial practice are explored.